Effects of Frozen Storage Temperature and Duration on Changes in Physicochemical Properties of Beef Myofibrillar Protein - Shuyi Qian; Xia Li; Hang Wang; Waris Mehmood; Chunhui Zhang; Christophe Blecker (Journal of Food Quality)
This study aimed to address the effects of frozen storage temperature and duration on the changes in physicochemical properties of beef myofibrillar protein. The beef was stored at −1, −6, −9, −12, and −18°C for 28, 84, 126, 168, and 168 days, respectively. The myofibrillar protein of beef samples denatured gradually with the extention of storage period. Regarding the samples stored at temperature range of −12∼−1°C, higher storage temperature resulted in more severe denaturation (the myofibrillar protein exhibited lower sulfhydryl content, Ca2+-ATPase activity, ionic bonds, hydrogen bonds, and higher surface hydrophobicity). Particularly, difference in −12 and −18°C did not yield significant effects upon the protein properties throughout 168-day storage P>0.05. These results indicated that lowering freezing temperature may not minimize myofibrillar protein denaturation in a limited storage duration, which was also confirmed by the quality properties of beef.